THE INFLUENCE OF WORK CULTURE, INCENTIVES, JOB CHARACTERISTICS ON EMPLOYEE DISCIPLINE AND PERFORMANCE OF CV. JAYA KARYA IN RANTAU, TAPIN REGENCY - Rahmawati, Rahmawati; Anthonius Junianto Karsudjono (Jurnal Ekonomi, 2020)
This study aims to determine the Influence of Work Culture, Incentives, Job Characteristics on Discipline and Performance of CV. Jaya Karya in Rantau, Tapin Regency. The method used in this study is a quantitative method, with a population of 102, a sample of 102 people and the data analysis technique in this study uses Partial Least Square (PLS). PLS is a Structural Equation Modeling (SEM) equation model with an approach based on variance or component-based structural equation modeling. The results of this study indicate that (1) Work Culture has no and no significant effect on Discipline (2 Incentive variables have no positive and significant effect on Discipline (3) Job Characteristics variable has a positive and insignificant effect on Discipline (4) Work Culture variable has a positive and significant effect on Discipline not significant to performance (5) the Incentive variable has a positive and insignificant effect on performance (6) the Job Characteristics variable has a positive and significant effect on performance and (7) the Discipline variable has a positive and significant effect on performance.